Effect of changes in the thickness of a perforated plate of the heat exchanger on its structural stability. - Chudzik, Agnieszka; Świniarski, Jacek (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2004)
One of the most important elements of heat exchangers are perforated bottoms. These are perforated plates of significant thickness, in which heating cartridge pipes are mounted. For the designers of heat exchangers, the strength analusis of the connection between the elements, which allows for the determination of the state of stress and calculation of displacements of the perforated bottom after fixing the pipes in it, is of special importance. It results from carried out computations that the maximum reduced stresses in the perforated bottom are significantly lower than the values of admissible stresses. In this paper, computations of stresses and strains for various thicknesses of the perforated bottom have been presented. As a results of a decrease in the thickness of the perforated bottom, its deflectionincrease, and thus the heating system pipes are more exposed to strains and losses of stability.

Jednym z istotnych elementów wymiennika ciepła są dna sitowe - płyty perforowane o znacznej grubości, w których zamocowane są rurki wkładu grzewczego. Dla konstruktorów wymienników ciepła istotna jest analiza wytrzymałościowa połączenia pozwalająca na określenie stanu naprężeń oraz obliczenie przemieszczeń dna sitowego po zamocowaniu rurek. Z przeprowadzonych obliczeń wynika, że maksymalne naprężenia zredukowane w dnie sitowym są dużo niższe od wartości naprężeń dopuszczalnych. W pracy przedstawiono obliczenia naprężeń i odkształceń dla różnych grubości dna sitowego. Na skutek zmniejszenia grubości dna sitowego zwiększa się jego napięcia, przez co rurki wkładu grzewczego bardziej są narażone na utratę stateczności.
Wpływ zmian grubości płyty perforowanej wymiennika ciepła na stateczność konstrukcji.
Keywords: finite element method; heat exchangers; heating pipes; wymiennik ciepła; płyta perforowana; stateczność; dna sitowe; wkład grzewczy; wytrzymałość połączeń